ANALISIS SISTEM DAN PROSEDUR AKUNTANSI ASET PADA DINAS PENDAPATAAN PENGELOLAAN KEUANGAN DAN ASET DAERAH KABUPATEN KEPULAUAN SANGIHE - Makitulung, Chriswanto Ignatius; Ilat, Ventje; Runtu, Treesje (Universitas Sam Ratulangi, 2019)
An asset is a resource that is absolutely necessary for the conduct of the Government. Government assets can be classified as financial assets and non-financial. Financial assets include cash, accounts receivable and investment. While the nonfinancial assets consist of assets which can be identified and which could not be identified. Intangible assets in the form of asset inventory (asset smoothly) and fixed assets, which in laws-known as an invitation of goods belonging to the country/region (BMN). The purpose of this research is to know the systems and procedures of Accounting Assets At the service of the Financial management of Income And assets of the Sangihe Islands Regency Area, with research methods used, are methods of data analysis that is descriptive. The results of the research on the system and procedure for an accounting of assets in the Sangihe Islands Regency indicates that the system and procedures of accounting assets are presented properly and in accordance with the government accounting system.